Sulfur-Oxidizing Bacteria Mediate Microbial Community Succession and Element Cycling in Launched Marine Sediment - Ihara, Hideyuki; Hori, Tomoyuki; Aoyagi, Tomo; Takasaki, Mitsuru; Katayama, Yoko (Frontiers in Microbiology, 2017)
A large amount of marine sediment was launched on land by the Great East Japan earthquake. Here, we employed both on-site and laboratory studies on the launched marine sediment to investigate the succession of microbial communities and its effects on geochemical properties of the sediment. Twenty-two-month on-site survey showed that microbial communities at the uppermost layer (0–2 mm depth) of the sediment changed significantly with time, whereas those at the deeper layer (20–40 mm depth) remained nearly unchanged and kept anaerobic microbial communities. Nine months after the incidence, various sulfur-oxidizing bacteria (SOB) prevailed in the uppermost layer, in which afterwards diverse chemoorganotrophic bacteria predominated. Geochemical analyses indicated that the concentration of metals other than Fe was lower in the uppermost layer than that in the deeper layer. Laboratory study was carried out by incubating the sediment for 57 days, and clearly indicated the dynamic transition of microbial communities in the uppermost layer exposed to atmosphere. SOB affiliated in the class Epsilonproteobacteria rapidly proliferated and dominated at the uppermost layer during the first 3 days, after that Fe(II)-oxidizing bacteria and chemoorganotrophic bacteria were sequentially dominant. Furthermore, the concentration of sulfate ion increased and the pH decreased. Consequently, SOB may have influenced the mobilization of heavy metals in the sediment by metal-bound sulfide oxidation and/or sediment acidification. These results demonstrate that SOB initiated the dynamic shift from the anaerobic to aerobic microbial communities, thereby playing a critical role in element cycling in the marine sediment.